Investigation of the effect of material's cell size with the fixed porosity on the efficiency of aerosol particle deposition. Issue 4 (February 2019) - Soloveva, O V; Solovev, S A; Khusainov, R R; Shubina, A S
Abstract: In this work, numerical simulation of the motion of dusty gas in the open cell foam material (filter's model) is carried out. The geometry of the porous material is created by a set of intersecting spheres arranged randomly in the space. Simulation of the gas flow in a porous medium without the use of averaged models is of great interest to scientists, and it is a detailed numerical simulation that takes into account the features of the internal structure. The studies were carried out for three characteristic pore sizes of 4, 5 and 6 mm of the filter cell to determine the size that is most preferable for the creation and use of porous filters operating at a given flow rate. Calculations have shown that a filter with the cell size of 4 mm has the highest quality factor, whereas a change in the deposition efficiency and the filter quality parameter for a casing with pore sizes of 5 mm and 6 mm differ insignificantly and much less than the parameters of the first case. The calculations performed are in good agreement with the semiempirical dependence of other authors.